Caracterización físico-química del subproducto bagazo de la caña de azúcar (Saccharum officinarum) como alternativa de manejo y aprovechamiento - Barreiro Zambrano, José Vicente (2024)
The physicochemical characterization of the sugarcane bagasse by-product (Saccharum officinarum) developed in the Agua Fría sector, Junín canton, was descriptive and analytical. In Phase I, the area was mapped with ArcGIS, field visits were conducted, and data was collected through surveys and interviews on bagasse generation. In Phase II, distilleries were characterized and samples of the by-product were taken following standards that include cleaning, drying and crushing of the biomass for the performance of proximal and elemental analyses. Finally, in Phase III, an environmental guide on the management and use of sugarcane bagasse was developed. In the Agua Fría sector, Junín canton, known for its production of currincho, as a traditional liquor, distilleries with sizes from 72 to 2074 square meters were identified, having to the Guayaca sugarcane variety is the predominant one (73%). Bagasse is the most common by-product, representing 50% of generation, although its management is poor, with 21.43% destined for composting and the rest generally burned. The proximal analysis of the bagasse shows high fiber (20.51%), low moisture (6.93%), and a high energy content (2579.63 Kcal/Kg). Elemental analysis reveals a high carbon (41.81%) and carbohydrate content, but low nitrogen (0.54%) and a C/N ratio of 80.91. The environmental guide presented alternatives such as controlled burning, briquette production, and the use of bagasse in animal feed and soil improvement, highlighting the need to optimize its management.